Hubungan Perilaku Caring dengan Pencegahan Risiko Infeksi di Rumah Sakit Islam Sultan Agung - Najla Nailah Qurratu’Ain; Moh Abdur Rouf; Dyah Wiji Puspita Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
From Swanson’s Caring theory, one of the caring indicators can be taken, namely knowing, which is an effort to know and understand events in needs and expectations but focuses on patients. Not only knowing needs and expectations but also focusing on efficient and effective care and treatment. Poor knowing of patient care can cause infection transmission. Therefore, nurses are required to have knowledge and be able to prevent the risk of infection. From poor nurse caring, it is possible for nurses to be affected which can be detrimental to nurses. If nurses carry out service tasks in accordance with SOP, they can reduce the risk of infection at the standard level set in hospitals. The purpose of this study was to determine caring bahavior with preventing the risk of infection in hospitals. This study used a sampling technique using a total sampling of 100 respondents using the spearman rank test. The results of this study were that most nurses were female, 79 people (79%), 51 nurses (51%) had good caring behavior, 97 nurses (97%), and 98 nurses (98%) were high in preventing the risk of infection. Conclusion, there is a relationship between caring behavior and prevention of infection risk at Sultan Agung Islamic Hospital Semarang by looking at the p-value of 0,000 the spearman rank correlation value is r 0,344 which indicates that the level of correlation strength is moderate with a positive correlation direction.